2010
DOI: 10.1152/ajprenal.00736.2009
|View full text |Cite
|
Sign up to set email alerts
|

Regulated oxygen sensing by protein hydroxylation in renal erythropoietin-producing cells

Abstract: The kidney is a major site of systemic oxygen sensing, regulating blood erythrocyte and hence oxygen content by hypoxia-inducible erythropoietin (Epo) expression. A constant ratio between blood perfusion and oxygen consumption, a stable corticomedullary oxygen gradient, and a relatively low tissue Po(2) are the prerequisites for the function of renal Epo-producing and oxygen-sensing (REPOS) cells, which are located in the juxtamedullary cortex. In kidney disease, renal oxygen consumption is decreased, leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 145 publications
2
87
0
3
Order By: Relevance
“…25 In this context, EPO may play tissue-specific physiologic roles possibly unrelated to erythropoiesis such as modulation of angiogenesis and cell survival. 26,27 The molecular pathways involved in the control of oxygen sensing and leading to EPO synthesis have been fully elucidated in recent years. 27 In vivo studies in rats as well as in vitro studies on EPO-producing cell lines clearly showed that EPO production depends on HIF-2a activation, 7,21,22 which, in turn, is modulated by the hydroxylation of its proline residues by PHD2.…”
Section: Discussionmentioning
confidence: 99%
“…25 In this context, EPO may play tissue-specific physiologic roles possibly unrelated to erythropoiesis such as modulation of angiogenesis and cell survival. 26,27 The molecular pathways involved in the control of oxygen sensing and leading to EPO synthesis have been fully elucidated in recent years. 27 In vivo studies in rats as well as in vitro studies on EPO-producing cell lines clearly showed that EPO production depends on HIF-2a activation, 7,21,22 which, in turn, is modulated by the hydroxylation of its proline residues by PHD2.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, during the past decade a large number of PHD2-interacting proteins have been discovered, including both upstream regulators and downstream targets of PHD2, substantially increasing the complexity of the PHD/HIF oxygen-sensing regulation pathway. 7 Moreover, PHD2 has been reported to have hydroxylation-independent gene regulatory functions. [35][36][37] Another category, including the PHD2-R398X mutation and three other PHD2 truncated mutations described previously, 12 can be compared to the VHL truncation mutations (VHL disease type 1) which are not associated with the development of pheochromocytomas.…”
Section: Discussionmentioning
confidence: 99%
“…For example, renal and hepatic erythropoietin is regulated by the HIF-2α subunit in vivo. [4][5][6][7] Germline mutations in genes involved in the HIF pathway have been reported in association with syndromes that predispose patients to both neoplasms and/or congenital secondary erythrocytosis. 8 The most frequent mutations involve the VHL tumor suppressor gene.…”
Section: Introductionmentioning
confidence: 99%
“…Physiologically, increased systemic erythropoiesis is a major adaptation to hypoxia. The reduced tissue oxygen level is sensed mainly by the kidney, resulting in increased production of EPO, a key regulator of erythropoiesis (78). EPO binds to EPO receptors on the surface of erythroid progenitors (79), where it prevents their apoptosis and induces the proliferation and differentiation into rbcs (80,81).…”
Section: Erythropoietic Activity Suppresses Hepcidin Expressionmentioning
confidence: 99%